The Influence of Product Design, Price, and Promotion on Consumer Buying Interest (Case Study on Convection of Alvin Jaya Collection in Bandung Regency) - Dede Hertina; Intan Dewi Yuli Yutika (Universitas Batanghari, 2023)
This study aims to determine the influence of product design, price,, and promotion on consumer buying interest. The object of this research is Alvin Jaya Collection Convection in Bandung Regency. This research method uses a descriptive method and the research uses quantitative data. The population in this study are consumers of Alvin Jaya Collection. The sampling technique uses non-probability sampling with accidental sampling techniques. This study used a sample of 60 respondents. The research result stated that product design variables partially did not effect on purchase intention. Meanwhile, the price, and promotion variables partially have a significant impact on purchase intention. Product design, price,, and promotion variables have a significant effect on purchase intention, simultaneously.